The order Tethyida (Porifera) in California: taxonomy, systematics, and the first member of the family Hemiasterellidae in the Eastern Pacific - Turner, Thomas L. (Zootaxa, 2020)
Sponges (phylum Porifera) are ubiquitous inhabitants of marine ecosystems and have been shown to provide substantial ecosystem services. Despite this ecological importance, the sponge fauna in California has received little study. Here I use a collection of kelp forest sponges to describe the diversity of the order Tethyida in California. This order contains the genus Tethya, which has been included in long-term ecological monitoring projects. I show that Tethya vacua is a junior synonym of Tethya californiana, and thus all Tethya populations known in California belong to a single species. Genetic data from California’s only Timeidae, Timea authia, indicate that this species is in fact in the Tethyidae and is the third known member of the genus Tethytimea. I also describe the first member of the family Hemiasterellidae from the Eastern Pacific, Galaxia gaviotensis gen. nov. sp. nov. By combining field photographs, morphological taxonomy, and phylogenetic analysis of these samples, this work will facilitate future efforts to understand the evolution of this order and the ecological role of sponges in the California kelp forest.